Analysis of the Tax Burden and Its Impact on Ensuring the Stability of the Economy - Shokhista Akhunova; Gulbahor Sultanova (Genius Publishing Group, 2023)
In the conditions of modernization of the economy, the tax policy is important in solving problems related to improving the activity of enterprises, including increasing their production efficiency, stabilizing the economy, and strengthening the financial situation of small businesses and private entrepreneurs. The article, a theoretical study of the current state of ensuring the stability of the state tax policy in the context of economic reforms, identification of existing problems and a specific proposal for the improvement of the new tax policy taking into account the existing traditions of the country in the implementation of economic reforms and structural changes in our Republic and comments were made.
Keywords: economic stabilization; small business and private entrepreneurship